PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY DENGAN MENGGUNAKAN MEDIA MIND MAPPING UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA SISWA KELAS VII4 SMP NEGERI 17 PEKANBARU - Fitriya, Anisa; Yustina, Yustina; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Experimental research had been conducted to improve science learning motivation of class VII4 students of JHS 17 Pekanbaru by using model guided inquiry using mind mapping. This pre-experimental design study was conducted in September-October 2018 with a study population of all students in class VII4 of JHS 17 Pekanbaru and a sample of students of class VII4, amounting to 37 people. The parameters in this study are science learning motivation consists of 4 indicators namely, Attention, Relevance, Confidence and Satisfaction. The results of this study indicate that treatment in the experimental class has an effect on increasing science learning motivation of class VII4 students showed: 1)Attention, student motivation experienced an increase in initial and final motivation of 2.43(low) to 3.24(moderate) with N-gain 0.51(medium. 2)Relevance, students' motivation experienced an increase in initial and final motivation which was 2.50(low) to 3.50(moderate) with N-gain 0.66(moderate). 3)Confidence, student motivation experienced an increase in initial and final motivation of 2.10(low) to 3.10(moderate) with N-gain 0.50 (moderate). 4)Satisfaction, motivation of students experiencing an increase in initial and final motivation, namely 2.30(moderate) to 3.60(moderate) with N-gain of 0.76(high). Based on the analysis of the average value of all the initial motivational indicators of 2.35(low) there was an increase in the average value of all indicators at the final motivation of 3.36 with N-gain of 0.60(moderate).It can be concluded that the application of the model guided inquiry using mind mapping has the effect of increasing the learning motivation of science students of class VII4 of JHS 17 Pekanbaru.Key Words: Guided Inquiry, Mind Mapping, Motivation